Characterization of Genes Responsible for the CO-Linked Hydrogen Production Pathway in Rubrivivax gelatinosus - Vanzin, Gary (American Society for Microbiology (ASM), 2010)
Upon exposure to carbon monoxide, the purple nonsulfur photosynthetic bacterium Rubrivivax gelatinosus produces hydrogen concomitantly with the oxidation of CO according to the equation CO + H(2)O ↔ CO(2) + H(2). Yet little is known about the genetic elements encoding this reaction in this organism. In the present study, we use transposon mutagenesis and functional complementation to uncover three clustered genes, cooL, cooX, and cooH, in Rubrivivax gelatinosus putatively encoding part of a membrane-bound, multisubunit NiFe-hydrogenase. We present the complete amino acid sequences for the large catalytic subunit and its electron-relaying small subunit, encoded by cooH and cooL, respectively. Sequence alignment reveals a conserved region in the large subunit coordinating a binuclear [NiFe] center and a conserved region in the small subunit coordinating a [4Fe-4S] cluster. Protein purification experiments show that a protein fraction of 58 kDa molecular mass could function in H(2) evolution mediated by reduced methyl viologen. Western blotting experiments show that the two hydrogenase subunits are detectable and accumulate only when cells are exposed to CO. The cooX gene encodes a putative Fe-S protein mediating electron transfer to the hydrogenase small subunit. We conclude that these three Rubrivivax proteins encompass part of a membrane-bound, multisubunit NiFe-hydrogenase belonging to the energy-converting hydrogenase (Ech) type, which has been found among diverse microbes with a common feature in coupling H(2) production with proton pumping for energy generation.